AN ANALYSIS ON EXTERNAL FACTORS INFLUENCING STUDENTS ENGLISH LEARNING ACHIEVEMENTS - Risfayanti, Lira; Sofian, H.; Husin, Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The aim of this research is to describe the dominant external factors influencing studentsâ€™ English learning achievements and to investigate how is the correlation of external factors toward studentsâ€™ English learning achievements of eleventh grade students of SMAN 1 Sungai Kakap in academic year 2013/2014. The researcher applied descriptive quantitative study using a correlation study in conducting this research. The data in this research were collected by using questionnaire with Likert-scale and the document of the studentsâ€™ English learning achievements in the first semester in the academic year 2013/2014. The result of research finding shows that the dominant external factors are teacher factor and classroom interaction factor. The percentage of teacher factor is 80.3% and classroom interaction is 74.3%. The computation also found that the correlation between external factors and English learning achievement was categorized as high to very high (2.56). It means that the alternative hypothesis â€œThere is a significant influence of external factors toward studentsâ€™ English learning achievementâ€ is accepted. Keywords: External factors, students English learning achievements Abstrak: Tujuan penelitian ini adalah untuk menjelaskan faktor eksternal dominan yang mempengaruhi hasil belajar siswa pada mata pelajaran Bahasa Inggris dan untuk mengetahui bagaiman korelasi antara faktor eksternal terhadap hasil belajar siswa pada mata pelajaran bahasa Inggris pada siswa kelas XI SMAN 1 Sungai Kakap di tahun ajaran 2013/2014. Peneliti menerapkan penelitian deskriptif kuantitatif dengan menggunakan metode korelasi. Data-data dalam penelitian ini diambil menggunakan kuesioner dan dokumentasi rapor siswa kelas XI semester 1 tahun ajaran 2013/2014. Hasil penelitian menunjukkan bahwa faktor eksternal yang dominan adalah faktor guru dan faktor interaksi kelas. Persentase faktor guru sebesar 80.3% dan persentase faktor interaksi kelas sebesar 74.3%. Hasil peneitian juga menunjukkan korelasi antara faktor eksternal dan hasil belajar siswa pada mata pelajaran bahasa Inggris dikategorikan dalam korelasi yang sangat tinggi yaitu mencapai angka 2,56. Itu berarti alternatif hipotesis, yakni â€œTerdapat pengaruh yang signifikan dari faktor eksternal terhadap hasil belajar siswa dalam mata pelajaran bahasa Inggrisâ€ dapat diterima. Kata Kunci: Faktor eksternal, hasil belajar siswa